A homogeneous atomic layer MoS2(1−x)Se2x alloy prepared by low-pressure chemical vapor deposition, and its properties. Issue 2 (9th December 2016) - Umrao, Sima; Jeon, Jaeho; Jeon, Su Min; Choi, Young Jin; Lee, Sungjoo
Abstract : The growth mechanism of large-area atomic MoS2(1− x ) Se2 x alloys grown with controlled morphologies using a low-pressure chemical vapor deposition (CVD) method. Abstract : We report the growth of large-area monolayer MoS2(1− x ) Se2 x alloys with controlled morphologies using a low-pressure chemical vapor deposition (CVD) method. MoS2(1− x ) Se2 x alloys with different morphologies, created using the same growth time, have been observed by controlling the gaseous MoO3 precursor on substrates placed in regions with different temperatures. TEM observations clearly reveal that the as-synthesized monolayer MoS2(1− x ) Se2 x alloy is crystalline, with a hexagonal structure. XPS, Raman mapping, and EDS mapping clearly show the homogeneous substitution of ∼2 atomic weight % Se through the whole crystal. Compared with a pristine CVD-grown monolayer of MoS2, the optical band gap differs by 4.52%, from 1.77 eV to 1.69 eV. Additionally, back-gated transistors fabricated on the monolayer MoS2(1− x ) Se2 x alloy exhibit n-type behavior at a current on/off ratio of ∼10 4 and a high mobility value of 8.4 cm 2 V −1 s −1 .